(untitled) (Informatica, 2023)
The tourism industry is all around keeping tourists happy, occupied and equipped with the things they need during their time away from home. On the other hand, mobile technologies have a considerable impact on user experience, particularly in the tourist and entertainment areas. This paper presents a tourist and entertainment-related mobile application. It utilizes a personalized experience approach and seeks to provide good user experiences by making it adaptable to their unique interests while considering many criteria such as the user’s gender, age, location, and other characteristics. The system will propose locations to visit or activities to do in any city to the user. As the user continues to use the application, the suggestions offered will constantly be improved; it will learn more about the user’s preferences by recording the user’s past and what they enjoy. The application implements and integrates two types of recommender systems, the item-item collaborative filtering algorithm and the user-user collaborative filtering algorithm. The user acceptance testing was conducted on 10 users from a variety of backgrounds and ages. Each participant has performed a set of 17 asks that covers the functionality of the application. Effectiveness results showed that about 70% of the tasks were completed without errors by all participants. And the tasks that were completed with some errors had an average of errors ranges from (0 - 0.4) which is a promising result when compared to the normal average number of errors per which is 0.7. Regarding the efficiency, results show that the longest completion time was in 3 tasks (register task, log-in, and edit profile) which is expected since they require the entry of detailed information. On the other hand, for the remaining tasks the average completion time was 5.4s which is accepted. User satisfaction was measured through a System Usability Scale (SUS) survey, the achieved score was 87.75 which is higher than the threshold to pass the SUS test which is 68, thus LOCUS has fulfilled the user satisfaction measure.